Effects of β-diketone antibiotics on F1-zebrafish (Danio rerio) based on high throughput miRNA sequencing under exposure to parents. (December 2016) - Zheng, Yuansi; Lin, Jiebo; Li, Jieyi; Zhang, Haifeng; Ai, Weiming; Wang, Xuedong; Dahlgren, Randy A.; Wang, Huili
Abstract: The toxicity of β-diketone antibiotics (DKAs), a class of ''pseudo-persistent'' environmental pollutants, to F0-zebrafish ( Danio rerio ) was investigated using 7-dpf F1-zebrafish miRNA sequencing and bioinformatics analyses. Based on relative expression, 47, 134 and 118 of 193 mature miRNAs were differentially expressed between control vs 6.25 mg/L, control vs 12.5 mg/L and 6.25 vs 12.5 mg/L treatments, respectively. Utilizing three databases, 2523 potential target genes were predicted, and they were assigned to 19 high-abundance KEGG pathways and 20 functional categories by COG analysis. Among 11 significantly differential expression and high-abundance miRNAs, the expression levels for 7 miRNAs (miR-144, -124, -499, -125b, -430b, -430c and -152) assessed by qRT-PCR were consistent with those determined by sRNA-seq. A potential network was plotted between 11 miRNAs and their target genes based on differential expression and binding effectiveness. The high degree of connectivity between miRNA-gene pairs suggests that these miRNAs play critical roles in zebrafish development. The expression of miR-124 and miR-499 in whole-mount in situ hybridization was in general agreement with those from qRT-PCR and miRNA-seq and were DKA concentration-dependent. DKA exposure induced severe histopathological changes and damage in F0-zebrafish ovary tissue, as reflected by an increased number of early developmental oocytes, irregular cell distribution, decreased yolk granules, cytoplasmic shrinkage, cell lysis in mature oocytes, and dissolution of internal corona radiata. Chronic DKA exposure affected reproduction of F0-zebrafish and development of F1-zebrafish. These observations demonstrate the toxic effect transfer relation across parent and their offspring, and enhance our understanding of drug-induced diseases. Highlights: Toxicity of DKAs to zebrafish was assessed by miRNA-seq and bioinformatics analyses. 193 mature miRNAs were differentially expressed in three comparison groups. A potential network was plotted between 11 positive miRNAs and their target genes. Expression of miR-124 and -499 in W-ISH was consistent with qRT-PCR and miRNA-seq. DKA exposure induced severe histopathological changes in F0-zebrafish ovary tissue.